Pengaruh Kebiasaan Belajar dan Dukungan Sosial terhadap Prestasi Akademik Mahasiswa Universitas PGRI Wiranegara - Nur Afifah; Sugeng Pradikto (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is the foundation for developing high-quality human resources. Students' academic success is influenced by internal factors, such as study habits, and external factors, such as social support. Study habits include time management, reading, and structured learning strategies, while social support involves attention, recognition, and assistance from family, friends, and the academic environment. This study aims to analyze the influence of study habits and social support on the academic achievement of students at Universitas PGRI Wiranegara. A quantitative research method with a causal-comparative design was employed. A sample of 93 active students from the 2021-2023 cohorts was selected using stratified random sampling. Data were collected through validated and reliable questionnaires and analyzed using simple linear regression. The results revealed that study habits and social support simultaneously contributed significantly to academic achievement. Study habits had a greater impact compared to social support. Social support creates a conducive learning environment, strengthens motivation, and enhances students' comfort in completing academic tasks. However, structured and disciplined study habits remain the key to academic success. These findings underscore the importance of developing effective study habits, such as time management and the use of effective learning methods, alongside strengthening social support to achieve optimal academic outcomes. Collaborative efforts between individuals, families, and educational institutions are essential.